Association between sleep duration and three obesity indicators among middle-aged and elderly adults: findings from the NHANES 2005–2014 - Jiang, Mengjin; Shou, Binyao; Shi, Lihua; He, Min (Frontiers in Nutrition, 2024)
Objective: Obesity has emerged as a worldwide problem. In recent years, it has been verified that there is an association between sleep duration and obesity indicators. This provides a new approach to control obesity. In this study, the relationship between duration of sleep and body mass index (BMI), waist circumference(WC), and waist-to-height ratio(WHtR) among Americans≥45 years old was investigated.: Data was collected from the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2014. The link between sleep duration and obesity indicators was analysed using multiple regression models and weighted smoothed curve fitting. Subgroup analysis was conducted to assess the consistency of the connection between sleep duration and obesity indicators across various groups.Results: This study involved 7118 males and 7265 females, with an average age of 62.09. After total adjustment, sleep duration was negatively correlated with BMI(β= -0.19, 95%CI: -0.26, -0.12) ,WC(β= -0.36, 95%CI: -0.53, -0.19)and WHtR(β= -0.27, 95%CI:-0.38, -0.17).Subgroup analyses revealed more significant negative associations between sleep duration and BMI, WC, and WHtR among non-Hispanic White participants, and those without diabetes and hypertension.Conclusions: Sleep duration was significantly negatively associated with BMI, WC, and WHtR, suggesting that longer sleep duration may contribute to lower obesity indicators in middle-aged and elderly Americans. Subgroup analysis showed that their negative correlation differed between races, diabetes, or hypertension status. However, additional prospective studies are required to validate these findings and investigate potential causal relationships.